Change is in the minds of the beholders - Ding, Zhonghui (Economic and business review, 2024)
Inspired by research on the “geography of thought” within social psychology, we present a cross-cultural comparative study of sociocognitive patterns between China, New Zealand, and Slovenia. We study COVID-19 risk perceptions and also explore predictions of economic trends under four specific economic scenarios. Our results show that the East-versus-West demarcation in terms of cultural boundaries is useful but insufficient to understand culturally driven predictions of economic trends. In times of economic downturn, such as the one caused by the recent COVID-19 pandemic, there seem to be universal tendencies towards pessimism. However, significant differences emerge in times of economic growth. Hence, while general human nature comes into play in times of economic adversity, greater differences in terms of “geography of thought” appear in times of economic expansion. For example, while Slovenians and the Chinese are similarly optimistic about economic expansion, New Zealanders seem to be more cautious in assuming the continuation of existing economic expansion. The study also reveals nuances in risk perception, with Slovenians more likely to see the pandemic as an opportunity compared to the Chinese and New Zealanders. Our findings offer valuable insights for policymakers in risk management, particularly in promoting economic resilience.
Keywords: China; economic flows; gospodarska gibanja; Kitajska; negotovost; New Zealand; Nova Zelandija; pandemic; pandemija; Slovenia; Slovenija; uncertainty